2015
DOI: 10.1515/cercles-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Learner beliefs about sociolinguistic competence: A qualitative case study of four university second language learners

Abstract: This article explores the beliefs about second language (L2) sociolinguistic competence of four university-level advanced L2 learners. It places particular emphasis on 1) how these university learners conceptualized L2 sociolinguistic competence; 2) how they thought about two different language learning contexts (viz., the L2 classroom versus study abroad) for their development of sociolinguistic competence; and 3) the L2 strategies they employed to develop their L2 sociolinguistic knowledge. The study found, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In addition, the students' identification of gaps regarding their knowledge of the upper and lower register markers (i.e., hyper-formal and vernacular sociolinguistic variants) is accurate in that it matches the patterns documented in their productive use of sociolinguistic variants, which featured the use primarily of formal and, to a lesser extent, informal sociolinguistic variants. This overuse of formal sociolinguistic variants is reminiscent of the findings of past studies [9] and may well reflect their educational input, their L2 sociolinguistic goals or overall L2-related goals, or other factors [6,7]. Regarding the learners' identification of what is missing in order for them to develop sociolinguistic competence, it is interesting to note that their calls for increased exposure to (authentic) use of French match the findings of previous research that has found it to be an effective way to develop such competence [10][11][12]17].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, the students' identification of gaps regarding their knowledge of the upper and lower register markers (i.e., hyper-formal and vernacular sociolinguistic variants) is accurate in that it matches the patterns documented in their productive use of sociolinguistic variants, which featured the use primarily of formal and, to a lesser extent, informal sociolinguistic variants. This overuse of formal sociolinguistic variants is reminiscent of the findings of past studies [9] and may well reflect their educational input, their L2 sociolinguistic goals or overall L2-related goals, or other factors [6,7]. Regarding the learners' identification of what is missing in order for them to develop sociolinguistic competence, it is interesting to note that their calls for increased exposure to (authentic) use of French match the findings of previous research that has found it to be an effective way to develop such competence [10][11][12]17].…”
Section: Discussionmentioning
confidence: 81%
“…Studies investigating FSL learners' metasociolinguistic knowledge have focused on exploring the effectiveness of providing learners with explicit instruction and/or engaging learners in metalinguistic reflection on the use of sociolinguistic variants. In such research, a clear distinction emerged between the knowledge of sociolinguistic variants and their actual use; in other words, between competence and performance [5][6][7]. The findings indicated that although explicit instruction was effective in helping learners develop competence, it did not automatically translate into performance.…”
Section: Fsl Learners' Metasociolinguistic Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…To conclude, analyses of this type offer valuable insight into the complex ways that classroom input, community exposure, and (inter-) systemic factors interact in their impact on the learning of variable grammar. Such insight adds to the already-rich interplay of factors pointed out by Carroll, and attested by and by Yang and Rehner (2015), and will hopefully serve to encourage further research.…”
mentioning
confidence: 65%
“…Although perceived as beneficial, immersion programs are challenged with respect to second language development, where an integrated language and content instruction approach is used (Cammarata, 2016;Lightbown, 2014). Few articles in the literature pertain to how Canadian French immersion students fare in higher education: most explore student engagement and sociolinguistic performance or competence (Mougeon & Rehner, 2014;Yang & Rehner, 2015). To our knowledge, the mental health of immersion students pursuing postsecondary education in a second language in a Canadian context has yet to be explored.…”
Section: Learning In a Second Languagementioning
confidence: 99%